USE OF MOBILE APPLICATION AS A NEW DIRECTION OF E-LEARNING - Ibragimova, Nayira (Журнал иностранных языков и лингвистики, 2023)
Foreign language education is currently becoming one of the basic components in the structure of competence in training of specialists. In this regard, significantly the role of a foreign language in preparation of specialists in educational institutions of higher education, in which the foreign language course is communicatively pragmatic mathematical and professionally oriented character.